Prospective self‐gated nonenhanced magnetic resonance angiography of the peripheral arteries. Issue 1 (5th March 2012) - Offerman, Erik J.; Koktzoglou, Ioannis; Glielmi, Christopher; Sen, Anindya; Edelman, Robert R.
Abstract Most nonenhanced MRA techniques for evaluating peripheral artery disease (PAD) require cardiac synchronization through physiological gating. Electrocardiographic gating is the most popular method for cardiac synchronization; however, it is subject to interference from switching magnetic field gradients and radiofrequency pulses. A method is described for self‐gated nonenhanced MRA that does not require the use of electrocardiographic gating. Imaging was prospectively triggered by detecting the acceleration of blood flow during systole with a reference‐less phase contrast navigator. The technique was implemented for nonsubtractive nonenhanced MRA using quiescent‐interval single‐shot MRA. The lower extremity peripheral arteries of eight healthy subjects were imaged using electrocardiographic‐, pulse‐, and self‐gated quiescent‐interval single‐shot. Self‐gated quiescent‐interval single‐shot triggered with 99% accuracy. There were no significant differences in relative contrast, contrast‐to‐noise ratio, or image quality between self‐gated and electrocardiographic‐gated quiescent‐interval single‐shot MRA (P > 0.05). Image quality with pulse gating was inferior. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.